Evaluation Technologies of Students’ Reading Literacy and Communicative Competence Skills in Teaching Language - V, Musaeva; M. B., Onolbayev; Sakhipzhamal, Uzakpayeva; Zhanar , Karmenbayeva; N.A., Maraimova (Journal of Ecohumanism, 2025)
Life itself proves the effectiveness of using assessment to provide quality education to the young generation and to improve the educational process of the school. Therefore, the primary goal of teaching the language to be teaching in a communicative direction and make the students to improve their reading abilities as well. Communicative method is implemented through direct communication between the student and the teacher, forms the manner of speaking in a certain language, consists of the main system of main signs and principles characteristic of linguistic relations and methodological categories, combines effective ways of teaching the language, and practically uses the language as a means of communication. Communicative learning is formed in all forms of language activity - in choosing, speaking, reading, writing, because it ensures its implementation. The article deals also with the essence of students’ reading literacy and communication skills development and assessment that is the of great importance of teaching them to extract the necessary information in continuous and non-continuous texts and use it in their own speaking activities. The concept of competence, functional literacy and reader literacy is given as well. The data characterizing the quality of test tasks, as well as the results of testing the reading literacy and communication skills of Bishkek school students and ways to improve them are presented. After a contextual introduction in this article, an example of educational mediation aimed at developing skills keys to lifelong learning and global skills for the 21st century through the reading of a certain number of selected texts are being presented.